Germinação de esporos de Byssochlamys nivea e Alicyclobacillus acidoterrestris por alta pressão e temperaturas médias em suco de laranja integral - Ferreira, Glaucia Aparecida Mataveli (2013)
Byssochlamys nivea and Alicyclobacillus acidoterrestris are spoilage microorganisms of great importance to the juice industry, they are able to produce spores. In addition to supporting the heat treatment commonly used in pasteurization of juices, these spores can also be activated by heat anticipating the deterioration of these foods and causing major damage to the fruit juice industry. New technologies have emerged for food processing. One is the use of high pressure. However, even with this technology, these microorganisms are difficult to control. Therefore, new strategies have been search to minimize these problems. One of such strategy is the inactivation of these microorganismos in two steps. First, a pre-treatment aims to sensitize the microorganisms through activation of germination. . In the second stage, the treatment would aim to inactivate microorganisms sensitized. However, data are needed to describe the levels of temperature and pressure necessary to sensitize these microorganisms. In this study, we used a combination of temperature followed by high pressure in order to test the behavior of B. nivea and A.acidoterrestris spores. Temperatures ranging from 46.6 to 63.4 °C for twenty minutes, followed by high-pressure ranging between 300 and 500 MPa for 5 to 15 minutes constituted the central composite rotational design (CCRD). For germination of B. nivea, the most significant factor (p<0.05) was high pressure, higher the pressure, greater the germination, reaching a maximum at 500 MPa. For germination of Alicyclobacillus acidoterrestris spores, temperature was the most significant factor (p<0.05), following the trend of higher the temperature, higher the germination of spores